Optimizing pineapple production under waterlogged soil condition in low input management using adequate ridge tillage height and plant density - Georges Marius Etame Kossi; Honore Djonko Beyegue; Alexis Boukong; Rose Germaine Ossogo; Lionel Lidjo (Frontiers in Plant Science)
Pineapple production is greatly hindered by waterlogging. This condition reduces the profitability of pineapple producer in areas frequently under temporary or permanently waterlogging soil condition. This situation weakens pineapple production and accentuate poverty in rural small-scale pineapple family producers, imbalance diet of consumer and high failure risk for young entrepreneur engage in transformation and commercialization of pineapple fruits. This study investigates the potential of ridge height and planting density on the growth and yield of Ananas comosus in waterlogged soil conditions. A split-plot design was employed, featuring three levels of ridge height (15 cm, 30 cm, and 45 cm) and two planting densities (27,777 and 57,142 plants.ha1) with four replications. Data was collected on shoot and root at growth, yield formation and harvest stage. The results indicated that a ridge height of 30 cm significantly enhanced root development, leaf area, and fruit yield, achieving an increase of 149% in yield with crown compared to 15 cm ridges. A ridge height of 45 cm creates a capillary barrier approximately 15 to 20 cm below the top of the ridge, which alters water movement within the soil during both wet and dry periods. Additionally, increased planting density resulted in improved resource utilization without adversely affecting growth parameters. The highest fruit yield of 86.9 t.ha-1 was recorded at 30 cm ridge height with a density of 57,142 plants.ha1, demonstrating the potential of optimized agroecological practices in enhancing pineapple production in waterlogged conditions. Incorporating soil moisture sensors, as noted in recent studies, could optimize water management and prevent water stress, contributing to more stable yield outcomes. Appropriate ridge height and optimal plant density optimize resource use by pineapple plant in waterlogging soil condition.